Retinal images in optomechanical eye model with monofocal intraocular lens - Jóźwik, Agnieszka; Nowak, Jerzy; Siedlecki, Damian; Zając, Marek; Zarówny, Józef (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Intraocular lens (IOL) is an artificial lens implanted into the eye. It usually replaces the existing crystalline lens, which is clouded over due to a cataract. In order to evaluate the optical performance of different IOLs an optomechanical model of human eye was developed. This model closely reproduces anatomical and optical properties of the average human eye. This makes it possible to measure the optical performance of different types of intraocular lenses and to estimate the influence of their location in eye on quality of vision. Four monofocal intraocular lenses were taken for analysis. The analysis of the quality of retinal images was carried out by means of either qualitative image comparison or physical quantities estimation. The analysis of LSF and MTF shows that the performance of the lenses tested changes slightly with differences in their design and/or material.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 593-605
Keywords: optyka; intraocular lens (IOL); artificial eye model; imaging quality; cataract